THE CORELLATION BETWEEN STUDENTS’ HABIT IN LISTENING ENGLISH SONGS TO THEIR VOCABULARY MASTERY AT CITRA BERKAT SENIOR HIGH SCHOOL BOGOR - Eriana Azzahra Putri (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
The aim of this research is to determine the correlation between students' habits of listening to English songs and their vocabulary mastery. This researcher used a correlation method using a quantitative approach. There are the two variables in this research. Students' habits of listening to English songs as independent variable (variable X) and Student Vocabulary Mastery as dependent variable (variable Y). The result from this research is significant correlation between students’ habit in listening English song is 0.02. Whereas 0.05< hypothesis is accepted, 0.05> hypothesis is denied, indicating a substantial association, it may be inferred between student’ habit in listening English song to their vocabulary mastery in Eleventh 1Citra Berkat Senior High School. Furthermore, to know the category of the correlation is from correlation category table, the result is 0,579. It can be concluded that the correlation between students’ habit in listening English song Strong enough the answers to the multiple-choice questions on vocabulary mastery and listening between students’ habits. This indicates that they can increase their vocabulary knowledge by making it a habit to listen to English songs.